Immediate clinical and haemodynamic benefits of restoration of pulmonary valvar competence in patients with pulmonary hypertension. Issue 8 (27th March 2009) - Lurz, P; Nordmeyer, J; Coats, L; Taylor, A M; Bonhoeffer, P; Schulze-Neick, I
Abstract : Objective: To analyse the potential benefit of restoration of pulmonary valvar competence in patients with severe pulmonary regurgitation (PR) and pulmonary hypertension (PH) associated with congenital heart disease. Design: Retrospective study. Setting: Tertiary paediatric and adult congenital heart cardiac centre. Interventions: Percutaneous pulmonary valve implantation (PPVI). Patients: All patients who underwent PPVI for treatment of PR in the presence of PH (mean PAP >25 mm Hg). Results: Seven patients with severe PH as a result of congenital heart disease and severe PR underwent PPVI. The valve implantation procedure was feasible and uncomplicated in all seven cases, successfully abolishing PR. There was a significant increase in diastolic (15.4 (7.3) to 34.0 (8.5) mm Hg; p = 0.007) and mean (29.7 (8.1) to 41.3 (12.9) mm Hg; p = 0.034) pulmonary artery pressures, and an improvement in NYHA functional class (from median IV to median III; p<0.008). Peripheral oxygen saturations rose from 85.9% (11.0%) to 91.7% (8.3%) (p = 0.036). Right ventricular (RV) volumes decreased (from 157.0 (44.7) to 140.3 (53.3) ml/m 2 ), while effective RV stroke volume increased (from 23.4 (9.3) to 41.0 (11.6) ml/m 2 ). During a median follow-up of 20.3 months (range 1.3–47.5), valvar competence was well maintained despite near systemic pulmonary pressures. None of the valved stents were explanted during follow-up. Conclusion: Trans-catheter treatment of PR in patients with PH is well tolerated and leads to clinical and haemodynamic improvement, most probably caused by a combination of increased pulmonary perfusion pressures and RV efficiency.